Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1124/jpet.116.236935
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted Murine Gut–to–Human Liver Signaling Alters Bile Acid Homeostasis in Humanized Mouse Liver Models

Abstract: The humanized liver mouse model is being exploited increasingly for human drug metabolism studies. However, its model stability, intercommunication between human hepatocytes and mouse nonparenchymal cells in liver and murine intestine, and changes in extrahepatic transporter and enzyme expressions have not been investigated. We examined these issues in FRGN [fumarylacetoacetate hydrolase (Fah2/2), recombination activating gene 2 (Rag22/2), and interleukin 2 receptor subunit gamma (IL-2rg 2/2) triple knockout] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 79 publications
2
27
0
Order By: Relevance
“…Okumura et al (2007) investigated the gene expression of human transporters in human hepatocytes of PXB mice and reported that the expression of OATP1B1/1B3 was strong, whereas that of oatp1b2 was weak. They also reported that the mRNA expression levels of hepatic transporters in the PXB mice and donor hepatocytes, and the levels of OATP1B1/1B3 in PXB mice were almost same as, 0.58-1.58 higher than, those in donor hepatocytes, which would indicate that the intestinal-liver axis does not affect expressions of OATPs in the mouse model compared with the other (Chow et al, 2017). Ohtsuki et al (2014) also conducted the protein qualification of transporters using an LC-MS/MS technique and showed similar expression levels for human transporters between human hepatocytes of PXB mice and 17 human liver biopsy samples, with no significant deference of the protein expression of OATP1B1/1B3 among three different donors (2, 5, and 10 years old) of hepatocytes of PXB mice.…”
Section: Discussionmentioning
confidence: 95%
“…Okumura et al (2007) investigated the gene expression of human transporters in human hepatocytes of PXB mice and reported that the expression of OATP1B1/1B3 was strong, whereas that of oatp1b2 was weak. They also reported that the mRNA expression levels of hepatic transporters in the PXB mice and donor hepatocytes, and the levels of OATP1B1/1B3 in PXB mice were almost same as, 0.58-1.58 higher than, those in donor hepatocytes, which would indicate that the intestinal-liver axis does not affect expressions of OATPs in the mouse model compared with the other (Chow et al, 2017). Ohtsuki et al (2014) also conducted the protein qualification of transporters using an LC-MS/MS technique and showed similar expression levels for human transporters between human hepatocytes of PXB mice and 17 human liver biopsy samples, with no significant deference of the protein expression of OATP1B1/1B3 among three different donors (2, 5, and 10 years old) of hepatocytes of PXB mice.…”
Section: Discussionmentioning
confidence: 95%
“…The mRNA expression levels of nuclear receptors, transporters and enzymes, particularly those responsive to Vdr (Chow et al, , ; Chow, Durk, Maeng, & Pang, ; Chow, Quach, et al, ; Chow, Sondervan, Jin, Groothuis, & Pang, ) and highly expressed in mouse tissues (Alnouti & Klaassen, ; Alnouti, Petrick, & Klaassen, ; Buckley & Klaassen, ; Buist & Klaassen, ; Cheng, Maher, Chen, & Klaassen, ; Lu & Klaassen, ) were examined. Total RNA extraction and cDNA synthesis procedures were performed as described (Chow et al, ; Chow, Durk, et al, ); specific primer sequences (Supplemental Table 2) were obtained from the literature (Chow, Durk, et al, ; Chow, Quach, et al, ; Chow et al, ; Chow et al, ; Chow et al, ; Durk et al, ; Gibson, Hossain, Richardson, & Aleksunes, ; Gong et al, ; Lee et al, ) or designed using Primer‐BLAST (Chow et al, ). The critical threshold cycle (C T ) values of target genes for mouse liver and kidney were normalized to that for cyclophilin while those of intestine (ileum) were normalized to that of villin, then expressed as the relative mRNA expression of the 0‐week of the normal vitamin D‐sufficient diet controls.…”
Section: Methodsmentioning
confidence: 99%
“…Human livers (n = 11) were provided by In Vitro ADMET Laboratories from the International Institute for the Advancement of Medicine (Edison, NJ) and the National Disease Research Interchange (Philadelphia, PA). These donor tissues were the same as those examined previously in another report, wherein information on the donors was described (Chow et al, 2017). 2.7 | Analysis 2.7.1 | Analysis of plasma 25(OH)D 3 , 1,25(OH) 2 D 3, calcium and PTH levels…”
Section: Human Liver Tissuementioning
confidence: 99%
“…These models usually have high variability due to the different degrees of humanization of the liver (partially human and partially mouse) whereas the other organs (e.g., intestine, kidney) are still murine in nature, and have different enzyme and transporter specificities from humans. It has been suggested that species incompatibility or miscommunication between other liver cells or tissues versus human hepatocytes may pose the main reason for deficiency, and the remaining mouse enzymes/transporters could be upregulated or have higher affinities to certain drugs (Chow et al, ). Humanized mice are prepared with a genetically immunocompromised background that may alter their metabolic and transport capabilities.…”
Section: Mechanisms On How Perpetrators Alter Pharmacokinetics Of Vicmentioning
confidence: 99%